No effect of intramuscular gold therapy on serological parameters of Helicobacter pylori infection in patients with rheumatoid arthritis: a 12 month prospective study. - ten Wolde, S (1994)
OBJECTIVES--To assess prospectively the influence of intramuscular gold therapy on Helicobacter pylori serology in patients with rheumatoid arthritis (RA). METHODS--Fifty patients with RA were started on intramuscular gold or chloroquine, as the control group and were followed serologically for H pylori infection for 12 months. RESULTS--Twelve patients treated with gold and eight control patients treated with chloroquine, all with serological evidence for H pylori infection, showed no significant decline of IgA and IgG anti-H pylori antibody levels or serum pepsinogen A and C levels. Total serum IgA and IgG levels declined significantly during gold therapy, while they remained unchanged during chloroquine therapy. CONCLUSIONS--Intramuscular gold therapy in patients with RA does not influence the serological parameters of H pylori infection.